2016
DOI: 10.14304/surya.jpr.v4n9.3
|View full text |Cite
|
Sign up to set email alerts
|

New polymorphism of the influenza virus resistance Mx1 gene in Iberian domestic pigs

Abstract: Mx1 (Myxovirus (Influenza virus) resistance 1, interferon-inducible protein p78) gene has been implicated in the resistance to a wide range of RNA viruses including influenza A in several species such as Sus scrofa. In the present study a 28-bp deletion in exon 14 of the Mx1 gene has been identified in Iberian domestic pigs but not in other domestic breeds neither in wild boars. The mutation produces a frameshift giving a protein with 6 amino acid substitutions and the extension of the C-terminal region with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…IFN-β, MX1, ISG15, and OASL have antiviral properties. Notably, the MX1 gene has shown resistance against different RNA viruses, including influenza A viruses, in both pigs and wild boars [39]. The ISG15 protein experiences significant upregulation in response to robust stimulation from viral infections within the body [40].…”
Section: Discussionmentioning
confidence: 99%
“…IFN-β, MX1, ISG15, and OASL have antiviral properties. Notably, the MX1 gene has shown resistance against different RNA viruses, including influenza A viruses, in both pigs and wild boars [39]. The ISG15 protein experiences significant upregulation in response to robust stimulation from viral infections within the body [40].…”
Section: Discussionmentioning
confidence: 99%
“…The last but important finding of the present work is that dietary OCM supplementation regulated the mRNA levels of antiviral proteins. The myxovirus resistance (MX) proteins are major effector molecules that prevent influenza-infected animals from developing severe phenotypes [ 25 ]. MX1 is an important downstream effector of type I interferons and has been reported to possess antiviral activity against a variety of RNA viruses [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The myxovirus resistance (MX) proteins are major effector molecules that prevent influenza-infected animals from developing severe phenotypes [ 25 ]. MX1 is an important downstream effector of type I interferons and has been reported to possess antiviral activity against a variety of RNA viruses [ 25 ]. Our results showed that dietary OCM supplementation increased the mRNA levels for both MX1 and MX2.…”
Section: Discussionmentioning
confidence: 99%